Aristotle’s Analysis of Perception - Biondi, Paolo (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2010)
AbstractThis paper examines Aristotle’s assertion found in Posterior Analytics II 19 that perception is of the universal. Through a study of De Anima II 6 and III 6-8, where Aristotle describes the objects of perception and of intellect, the author argues that, for Aristotle, human perception is always of the universal as it is found in the particular because the unity of the individual substance guarantees the unity of the act of perception. Consequently, the analysis into three perceptible objects is merely the result of Aristotle’s analytical method used to study the act of perception.